Escola de tempo integral para a formação do sujeito neoliberal : uma análise do programa de educação integral da Paraíba - Leite, Maria Eduarda Pereira (2023)
In 2016, the Comprehensive Education Program was implemented in the state of Paraíba, establishing full-time secondary education in the state's public schools. Although this public policy has been relatively successful, there are contradictions in that it is surrounded by networks of power relations, giving rise to different understandings. The aim of this thesis, therefore, is to investigate how public educational policies promoting full-time education contribute to students' education, from a neoliberal perspective. In this sense, it was necessary to understand, based on the dynamics of a state school, how the state of Paraíba, through the Full-Time Education Program, seeks to educate its students, within this neoliberal perspective, based on the idea of protagonism, autonomy, flexibility and curricular and management innovation. With this as our guiding objective, we carried out bibliographical and documentary research, as well as field observations and interviews with teachers, students, managers and those responsible for the project at regional level. Based on the data collected, the research showed that the implementation of the Paraíba Comprehensive Education Program meant, in several respects, a deepening of the business view of education, through the state's partnership with private sector entities to implement the policy, demonstrating that the role of the state in the relationship between education and development is to mediate this relationship through measures aimed at guaranteeing the reproduction of capital, in other words, the state articulates and conducts public policies, including educational ones, based on the assumptions of the private sector's logic, institutionalizing the guidelines stemming from the business agenda. It was also possible to observe that the discourses present in the official documents use terms that refer to an innovative and emancipatory ideology, however, when we analyze the data from a critical sociological perspective, we see that they reinforce the neoliberal traps of meritocracy that hold young people responsible and culpable for their own destinies, distancing the state from its constitutional responsibilities and from a truly emancipatory education that enables an autonomous identity. We have also shown that the implementation of the Comprehensive Education Program, by meeting the demands of neoliberalism, has implied a process of disqualification of Comprehensive Education, insofar as it has reduced school education to meeting the immediate demands of contemporary capitalist production relations. Finally, we would like to point out that the idea of comprehensive education in the Paraíba Comprehensive Education Program leads to the disarticulation of education as a social right in favor of an economistic idea of human formation that takes into account all of its diversity, in favor of the construction of a neoliberal subject.